FENG SHUI PADA TATA LETAK MASSA BANGUNAN DI KELENTENG SAM POO KONG - Marcella, Benedicta Sophie (Jurnal Arsitektur Komposisi, 2012)
Abstract: â€œKlentengâ€ is an Indonesian term for place of worship for Chinese traditional faiths in Indonesia. Sam Poo Kong temple is a heritage building located in Semarang. Chinese temple building is part of the China building architecture, thus Chinese temple apply the feng shui principals, so that people get the fortune, peace, and prosperity from the perfect balance with nature. In this research, to be conducted a review of the use of feng shui principles contained in the layout of the building mass. The research question that arises is "How the application of feng shui to the layout of the building mass in the Sam Poo Kong temple?" This research aims to determine the influence of feng shui contained in the layout of the building mass Sam Poo Kong temple in Semarang. This research use structuralizes qualitative methodology. Analysis process was done by comparing the theory of feng shui with field observations. The building layout, planes, and the filler elements apply the principles of feng shui and it has a good meaning, leads to happiness and welfare in life. Cultural influence of Islam, Buddhist, Hindu, and Chinese cultures convey the meaning and message to the user of the building, all for good purpose in human life. Based on the analysis it can be concluded that the meaning of the layout of the building mass on the Sam Poo Kong temple in accordance with feng shui theory and it brings prosperity.Keywords: feng shui, Sam Poo Kong Temple, the layout of the building massAbstrak: Kelenteng atau Klenteng adalah sebutan untuk tempat ibadah penganut kepercayaan tradisional Tionghoa di Indonesia pada umumnya. Kelenteng Sam Poo Kong merupakan bangunan cagar budaya yang terdapat di kota Semarang. Bangunan kelenteng termasuk dalam bangunan Cina, sehingga dalam tatanan bentuk bangunannya masih mempergunakan kaidah feng shui. Konsep feng shui adalah seni hidup dalam keharmonisan dengan alam, sehingga seseorang mendapatkan keuntungan, ketenangan, dan kemakmuran dari keseimbangan yang sempurna dengan alam. Dalam penelitian ini, akan dilakukan peninjauan penggunaan kaidah feng shui yang terdapat pada tata letak massa bangunannya. Pertanyaan penelitian yang muncul adalah â€œBagaimana penerapan fengshui pada tata letak massa bangunan di kawasan Kelenteng Sam Poo Kong?â€ Penelitian ini bertujuan untuk mengetahui pengaruh feng shui yang terdapat pada tata letak massa bangunan Kelenteng Sam Poo Kong di Semarang. Metodologi yang digunakan adalah strukturalis kualitatif. Proses analisis dilakukan dengan membandingkan teori feng shui dengan hasil observasi lapangan. Tata letak massa bangunan menerapkan kaidah feng shui serta memiliki makna yang baik, mengarahkan pada kebahagiaan serta keselamatan dalam kehidupan. Pengaruh budaya Islam, Buddha, Hindu, serta Kebudayaan Cina telah bercampur, menyampaikan makna serta pesan kepada pengguna bangunan, semua untuk tujuan kebaikan dalam hidup manusia. Berdasarkan hasil analisis maka dapat disimpulkan bahwa tata letak massa bangunan pada kawasan Kelenteng Sam Poo Kong sesuai dengan feng shui aliran bentuk dan mendatangkan kebaikan.Kata Kunci: feng shui, Kelenteng Sam Poo Kong, tata letak massa bangunan